Some New Exact Solutions for Time Fractional Thin-Film Equation (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, the invariant subspace method is utilized to obtain some new exact solutions for the time fractional thin-film equation. The fractional derivative in the considered equation is given in Remain-Liouville and Caputo senses. Some new invariant subspaces have been obtained that are not reported in the literature before.